THE ANALYSIS OF THE STRAIN STATE OF SHEAR ZONES IN TERMS OF TYPES OF SECONDARY FRACTURES: STATEMENT OF PROBLEM - Fyodor L. Yakovlev (Геодинамика и тектонофизика, 2015)
Introduction. In this publication, shear zones, being traditional objects of tectonophysical studies, are considered in terms of their strain states. This approach differs from a commonly applied one when shear zones are studied with consideration of stress fields. The difference of a stress field and a field of strain for a simple shearing has been already noted by the researchers (Figure 1). As is known, secondary fractures in natural shear zones and in experiments do not always correspond to structures which are theoretically predicted by stress field studies. The problem under investigation in this publication is which combinations of secondary structures are possible/impossible in specific emerging strain fields?Initial concept. The theoretical basis is the wellknown scheme of secondary fractures proposed by P. Hancock [1985]. His representation of combinations of structures (Figure 2) is arbitrarily compiled: some of the secondary fractures (such as thrusts and normal faults) can not exist simultaneously as this leads to opposite deformation results (Figure 3).Theoretical consideration of 2D strain in a shear zone. As a priority, all cases of elongation and shortening of the zone are theoretically studied in the constant volume of the zone. In previous studies, the situation was considered with additional compression or tension in the direction perpendicular to the shear zone (Figure 4), but not with elongation or shortening of the shear zone. The analysis of the strain state of the shear zone revealed that development of Riedel shears of R and R′ types (which are paired and identical in the stress field of pure shearing) can lead to opposite results in deformation of the zone. Shear cracks of R type cause elongation of the zone and reduction of the zone’s width (Figure 5). Shear cracks of R′ type can occur with shortening of the zone and increase in its width (Figure 6). Shear cracks of X and P types (which are also paired) demonstrate similar behavior: X cracks occur with lengthening of the zone, while P cracks occur with its shortening. Cracks of Y type, which go parallel to the zone, can be observed in both cases. Influence of increase or reduction of the shear zone’s volume on possible combinations of structures, including tension fractures and stylolithic fractures, is also considered. Combinations of secondary fractures revealed by the theoretical studies are tabulated (Table 1); six cases are distinguished with regard to active, possible and impossible structures. GEODYNAMICS & TECTONOPHYSICS PUBLISHED BY THE INSTITUTE OF THE EARTH’S CRUST SIBERIAN BRANCH OF RUSSIAN ACADEMY OF SCIENCES TectonophysicsExamples of combinations of secondary fractures in experiments and natural structures. Examples of echelon structures are considered in terms of the strain state of shear zones. In experiments, alternations of domains, wherein shear cracks of R and R′ types are developing along shear zone, are interpreted as a combination of domains with elongation and shortening of the medium (along the strike of the zone), while the total length of the zone remains unchanged (Figure 7). It is assumed that variations of widths of zones of influence of faults, that are observed in natural structure, and changes of amplitudes of displacement in seismogenic faults (Figure 8) are related to this phenomenon of alternation of domains wherein shear cracks of R and R′ types are developing, i.e. there is a relation to elongation and shortening of such domains of a fault zone. Structures of terminations of large faults of ‘horsetail’ and ‘fishbone’ types are interpreted as domains wherein shear cracks of R and R′ types develop as secondary faults under conditions of lengthening and shortening of the sides of the main fault (Figure 9). It is shown that shatter zones in the basalt detachment of the Vorontsovsky nappe are related to shear cracks of R type; they evidence elongation of the nappe’s body (Figure 10). In the scale of the given outcrop, a number of specific combinations of share cracks of P type and tension fractures are reviewed (Figure 11, 12, 13, 14, and 15). Structures with development of shear cracks of X type are specified; these are synthetic faults in the body of the landslide and echeloned normal faults in sides of regional shear faults in petroliferous structures of the Western Siberia (Figure 16).Theoretical research of zones of simple shearing in a massif which is subject to general deformation of pure shearing. Simple shearing zones, which are located in massifs which are subject to pure shearing, are a target of special theoretical studies. Under such conditions of the massif’s deformation, the length of shear zones in the massif will either increase or decrease, depending on  orientations of such zones relative to the axis of shortening (Figure 17). Assumptions of possible combinations of secondary fractures in such shear zones are made.onclusions. It is established that in a shear zone, cracks of R and R′ types can not develop in one domain as they lead to opposite deformation consequences. However, this has not been taken into account when describing shear zones in terms of stress fields. Concerning emerging deformations of a shear zone, it is revealed that cracks of R and X types are paired (in case of zone’s elongation), and cracks R′ and P types are in the opposite pair (case of zone’s shortening). The table of theoretically possible and impossible secondary fractures is compiled for a variety of deformation conditions of a shear zone. The problem of collecting data on stable combinations of echelon secondary structures, that occur in shear zones, and developing a systematic review of such combinations on the basis of concepts of the strain state of the shear zones is put forward. It is proposed to apply changes of shear zone length in modeling of these structures on equivalent materials.